Packing the court the rise of judicial power and the coming crisis of the Supreme Court - Burns, James MacGregor 1918-2014 (Penguin, 2009)
From renowned political theorist and Pulitzer Prize winner James MacGregor Burns, an illuminating critique of how an unstable, unaccountable, and frequently partisan Supreme Court has come to wield more power than the founding fathers ever intended.
Includes bibliographical references and index
Keywords: United States -- Supreme Court -- History; Geschichte; Political questions and judicial power -- United States; Judges -- Selection and appointment -- United States; USA